Generalized information matrix tests for detecting model misspecification - Richard M. Golden; Steven S. Henley; Halbert White; T. Michael Kashner (Econometrics, 2016)
Generalized Information Matrix Tests (GIMTs) have recently been used for detecting the presence of misspecification in regression models in both randomized controlled trials and observational studies. In this paper, a unified GIMT framework is developed for the purpose of identifying, classifying, and deriving novel model misspecification tests for finite-dimensional smooth probability models. These GIMTs include previously published as well as newly developed information matrix tests. To illustrate the application of the GIMT framework, we derived and assessed the performance of new GIMTs for binary logistic regression. Although all GIMTs exhibited good level and power performance for the larger sample sizes, GIMT statistics with fewer degrees of freedom and derived using log-likelihood third derivatives exhibited improved level and power performance.
Keywords: C12; C13; C15; C18; C52; 330; asymptotic theory; Information Matrix Test; specification analysis; logistic regression; simulation study; information ratio; misspecification